Carbonised macro-remains from a Germanic settlement in Jevišovka-Nová : a contribution to current archaeobotanical knowledge of the Roman period - Apiar, Jana (2022)
This book results from the lead author’s postdoctoral working activities at the Institute of Archaeology of the Czech Academy of Sciences, Brno, Research Centre for the Roman and Migration Periods. The book focuses on analysing and evaluating the archaeobotanical collection obtained as part of the rescue excavation conducted by the named institute in Jevišovka – Nová Street. It directly follows the lead author’s doctoral research results. One of the dissertation conclusions was the need to supplement the acquired results with a more detailed archaeobotanical analysis of individual sites, which are still scarce in the local scientific environment. The archaeobotanical analysis of the material from Jevišovka was an opportunity for supplementation and mutual comparison with previously obtained results